Social anxiety disorder : epidemiology, biology and treatment - Fink, Martin (Array, 2009)
The disease places a massive burden on patients lives, affecting not only their social interactions but also their educational and professional activities, thereby constituting a severe disability. Functional magnetic resonance imaging studies have repeatedly emphasized the central role of the amygdalae and insula in the neural circuitry of the disorder. Selective serotonin reuptake inhibitors (SSRI) are commonly accepted as first line therapy, however other substance classes like serotonin norepineprine reuptake inhibitors (SNRI), monoamine oxidase inhibitors (MAOI), benzodiazepines and several other agents have also proved effective. A combined treatment-approach including psychotherapy (e.g. cognitive behavioural therapy) may prove useful.